Analisa Website Puslit Indonesia Dengan Menggunakan Webqual Untuk Pengukuran Kualitas Website - . Nurhayati (Explore: Jurnal Sistem Informasi dan Telematika (Telekomunikasi, Multimedia dan Informatika), 2013)
Media websites are all available information on the Internet. Needs also use websites in need in an enterprise, companies can more easily promote their products using the website penjualan.Kualitas services in disseminating information on the sales website has become a very important requirement, as this may impact the level of subscriber satisfaction and community wide that will access the company's website. INDONESIA CV.PUSLIT website. INDONESIA Research Center or the IT Solution Center Indonesia is one of the companies engaged in the sale of which is highly dependent to the Internet. It is important for a website to be able to make the Research Center INDONESIA assessment of the quality of the website using the WebQual is one method or technique of measuring the quality of the website is based on the perception of the end user. This is because the Research Center is a company focused to serve the development of the product - software products (software or system) based Information Technology is marketed only through the website. This method is an extension of the widely used SERVQUAL prior to the measurement of service quality